2008
DOI: 10.1111/j.1468-0475.2008.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Transatlantic Differences in Labour Markets: Changes in Wage and Non-Employment Structures in the 1980s and the 1990s

Abstract: Rising wage inequality in the United States and Britain and rising continental European unemployment have led to a popular view in the economics profession that these two phenomena are related to negative relative demand shocks against the unskilled, combined with flexible wages in the Anglo-Saxon countries, but wage rigidities in continental Europe (‘Krugman hypothesis’). This paper tests this hypothesis based on seven large person-level data sets for the 1980s and the 1990s. I use a more sophisticated catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
7
1
Order By: Relevance
“…Over a similar period, Fitzenberger and Garloff (2008) analyze unemployment and wage inequality in West Germany and find no support for the Krugman hypothesis when looking at the relationship between within-cell wage dispersion and unemployment by cells. Their findings, however, carry no implications for the validity of the Krugman hypothesis for between-group differences in relative wages and unemployment, which are the focus of Card et al (1999) and Puhani (2008) as well as our study (Fitzenberger and Garloff 2008).…”
Section: Introductioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Over a similar period, Fitzenberger and Garloff (2008) analyze unemployment and wage inequality in West Germany and find no support for the Krugman hypothesis when looking at the relationship between within-cell wage dispersion and unemployment by cells. Their findings, however, carry no implications for the validity of the Krugman hypothesis for between-group differences in relative wages and unemployment, which are the focus of Card et al (1999) and Puhani (2008) as well as our study (Fitzenberger and Garloff 2008).…”
Section: Introductioncontrasting
confidence: 60%
“…Card, Kramarz, and Lemieux (1999) analyze a long-term change in the skill-specific wages and employment over the 1980s for France, Canada and the US, and reject the Krugman hypothesis when France and Canada are compared to the US. Puhani (2008), on the other hand, focuses on the relative wages and employment rates in the UK, the US, and Germany, and finds evidence in favor of the Krugman hypothesis for the 1980s and 1990s when Germany is compared to the US. Over a similar period, Fitzenberger and Garloff (2008) analyze unemployment and wage inequality in West Germany and find no support for the Krugman hypothesis when looking at the relationship between within-cell wage dispersion and unemployment by cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Krueger & Pischke (1997) for the US, and Card et al (1999) for the US, France and Canada found no impact of wage rigidity on the unemployment of the unskilled in relation to the unemployment of the skilled. In contrast, such a relation is found by Puhani (2008) who analyses and compares the cases of West Germany, Britain and the US. Assessing the impact of policies and institutions on employment and unemployment in OECD countries over the past decades, Bassanini & Duval (2006) find that high unemployment benefits and high tax wedges increase unemployment, whereas employment protection legislation has no significant impact and centralised and/or coordinated wage bargaining systems reduce unemployment.…”
Section: Empirical Impacts Of Labour Market Institutions Upon Unemplomentioning
confidence: 91%